Explaining variance and identifying predictors of children's communication via a multilevel model of single-case design research. (3rd May 2016) - Ottley, Jennifer Riggie; Ferron, John M.; Hanline, Mary Frances
Abstract: The purpose of this study was to explain the variability in data collected from a single-case design study and to identify predictors of communicative outcomes for children with developmental delays or disabilities ( n  = 4). Using SAS® University Edition, we fit multilevel models with time nested within children. Children's initial levels of communication and teachers' frequency of strategy use when directed at the children predicted children's communicative outcomes. These results indicate that teachers' implementation of evidence-based communication strategies, when directed toward children with disabilities, and the interaction between their use of the strategies and children's initial levels of communication predict children's communicative outcomes. Implications for research and practice are provided.